Horseshoe kidney - Nahm, Anna-Maria; Ritz, Eberhard (Nephrology, dialysis, transplantation, 1999)
The horseshoe kidney is one of the most frequent malformations of the urogenital tract. During normal development, the kidneys rotate in such a way that the ureters leave the kidney from its medial aspect and the axes of the kidneys diverge (Figure 1a); the horseshoe kidney is malrotated, i.e. the normal rotation of the kidney is incomplete, so that the ureters leave the kidney from its ventral aspect and the longitudinal axes of the kidneys converge (Figure 1b). Because the lower poles of horseshoe kidneys extend ventro-medially they can usually not be properly delineated. As the kidney cannot be visualized in its entirety, one common error is the diagnosis of a small kidney. The fused lower poles are connected by an isthmus (bridge), consisting either of renal parenchyma or fibrous tissue, which lies ventrally to the aorta. This constellation often leads to the erroneous diagnosis of a retroperitoneal tumour, particularly lymphoma.
Gesehen am 05.11.2021